Enhancing thermoelectric performance through acid-treated NbFeSb: a versatile approach for sustainable energy conversion - Kim, Minsu (2024)
Drop-casting has emerged as a promising and scalable technique for fabricating thermoelectric generators, suitable for energy harvesting and waste heat recovery applications. This study delves into the potential of thermoelectric drop-casting utilizing acid-treated NbFeSb, a half-Heusler material. The acid treatment notably reduces the particle dimensions of NbFeSb from a micro-scale to a nano-scale, thereby enhancing phonon scattering and diminishing thermal conductivity from 16 to 12 W/mK at room temperature. The formulation of the thermoelectric ink involves ethylene glycol as the solvent and polyvinylpyrrolidone (PVP) as an additive, meticulously optimized to enhance dispersion and rheological attributes. To systematically analyze the performances of the printed films, an investigation was conducted, varying the PVP concentration. Our findings indicate that a 20% PVP content yields the highest power factor, concurrently enhancing the Seebeck coefficient and electrical conductivity, while preserving reduction in thermal conductivity. The ink-printed films of acid-treated NbFeSb exhibited superior thermoelectric performance compared to pristine NbFeSb films, owing to the uniform distribution of nanoparticles and the absence of particle agglomeration. Furthermore, this study successfully fabricates a flexible thermoelectric generator (TEG) using acid-treated NbFeSb ink, demonstrating its potential integration into wearable devices and power generation systems. The TEG attains an open-circuit voltage of 88 mV across a temperature gradient of 40 K, with a peak output power of 8.1 mW. This study highlights the significant impact of thermoelectric drop-casting as an adaptable and efficient approach to enhance the thermoelectric performance of high-thermal-conductivity half-Heusler materials, opening new avenues for sustainable energy conversion technologies.